Double-patch and glue repair of a postinfarction left ventricular pseudoaneurysm. (February 2021) - Miyagawa, Atsushi; Okamura, Homare; Kitada, Yuichiro; Arakawa, Mamoru; Adachi, Hideo
An 85-year-old man with appetite loss, lightheadedness, and leg edema was referred to our institution. Computed tomography and transthoracic echocardiography revealed a left ventricular pseudoaneurysm with a maximal diameter of 80 mm and severe mitral regurgitation. Coronary angiography showed 90% stenosis and total occlusion of the left circumflex artery at segments 11 and 12, respectively. He was diagnosed with postinfarction left ventricular pseudoaneurysm and underwent patch repair using two bovine pericardium patches and biological glue, mitral valve replacement, and coronary artery bypass grafting. His postoperative course was uneventful.